Assessment of the Nature Interactions of ?-Amyloid Protein by a Nanoprobe Method - Melo-Hurtado, F; Caballero-Alvial, L (American Chemical Society, 2015)
We present a method based on atomic force microscopy (AFM) to assess the work of adhesion between the interfaces of gold AFM tips functionalized with three peptides derived from β-sheet breaker LPFFD [CLPFFD-NH2 (i0) and their isomers CDLPFF-NH2 (i1) and CLPDFF-NH2 (i2)], and the beta-amyloid protein (Aβ1-42). β-Amyloid protein was deposited onto a highly oriented graphite (HOPG) surface as protofibrils and fibrils. The presence of the residues Leu (L), Phe (F), and Phe (F), which are also present in the native sequence, confirm that the peptides are able to bind to the aggregates of Aβ1-42 fibrils and protofibrils. Force of adhesion data were directly obtained from the maximum force on retraction, and the work of adhesion was calculated from the Jhonson-Kendall-Roberts model (JKR-Model). Both the polar and dispersive contributions to the surface energy of the peptides i0, i1, and i2, as well as Aβ1-42 fibrils and protofibrils, were determined by means of measuring the contact angle and using the two-fluid method. The macroscopic energies of the functionalized gold surfaces do not differ significantly between isomers, which confirms the similar nature of the peptides i0, i1, and i2 but suggests that the macroscopic measurements are not able to distinguish specific sequences. The nanoprobe reveals a typical adhesion work value associated with the interaction of protofibrils with i0 and i2; this value is three times higher than that of i1. The difference is attributed to the hydrophobic nature of protofibrils, the predominant exposition of hydrophobic residues of the peptides i0 and i2, with respect to i1, and the degree of functionalization. i0 and i2 presented a slight adhesion with Aβ fibrils, which is associated with the exposed hydrophilic groups of these fibrils (onto HOPG) compared to the protofibrils. However, i1 showed interaction with both Aβ fibrils and protofibrils. For this, we propose an explanation based on the fact that the peptide i1 locates itself adjacent to the gold surface of the probe, concealing their hydrophobic groups and therefore decreasing the probability of interaction with Aβ fibrils and protofibrils. The peptide-gold nano probe represents a useful tool to study the nanobiointeractions of functionalized nanoparticles with amyloid aggregates. © 2014 American Chemical Society.